Retention in HIV Care Programs and Its Association with Comorbidity Incidence and Viral Load Reduction - Majid Alizadeh; Mohammad Rashidi Evandi; Maryam Jafar Sameri; Elham Senisel Bachari; Mohammad Kogani (Iranian South Medical Journal)
Background: The human immunodeficiency virus (HIV) remains a critical global public health challenge, contributing to a growing burden of comorbidities and diminished quality of life among affected individuals. This study aimed to examine the association between retention in HIV care programs and the occurrence of comorbidities, as well as its impact on viral load suppression. Materials and Methods: This descriptive-analytical study included 190 HIV-positive patients (out of 202 active records) aged over 18 years who were monitored at the Khorramshahr Behavioral Diseases Counseling Center between 2017 and 2022. Demographic data, treatment characteristics, and clinical information were extracted from medical records. Data were analyzed using SPSS software, with statistical tests including ANOVA and Pearson’s correlation coefficient. Results: The study found that 68.4% of the patients had high retention (attending>70% of scheduled visits), 26.3% had moderate retention (40–70%), and 5.3% had low retention (<40%). Higher retention was associated with increased CD4 counts and lower viral loads. Additionally, better socioeconomic status and higher education levels correlated with improved CD4 levels and reduced viral loads. Over half of the patients (55.3%) had at least one comorbidity, with hepatitis B, hepatitis C, and tuberculosis being the most prevalent. Conclusion: Retention in HIV care programs is linked to enhanced immune function (higher CD4 counts) and improved viral suppression. These findings underscore the need for comprehensive support programs to promote treatment adherence, manage comorbidities, and enhance the quality of life for individuals with HIV.